Effectiveness of an operating room master of science program based on Kirkpatrick's model. - Amiri, Mina; Momennasab, Marzieh; Yektatalab, Shahrzad; Hamidizadeh, Saeed; Rahimi, Zahra; Badiyepeymaiejahromi, Zohreh (Research & Development in Medical Education, 2022)
Background: Evaluation is one of the most critical issues in the training process. Kirkpatrick's model is one method in educational evaluation that can accurately evaluate programs. This study aimed to evaluate the effectiveness of an operating room master of scienc (MS) program om based on Kirkpatrick's model. Methods: This descriptive, cross-sectional study was conducted using convenience sampling with 46 students and graduates from the operating room MS degree at the Shiraz University of Medical Sciences in the academic year 2020-2021. A valid and reliable questionnaire with 47 items in three levels of reaction, learning, and performance was used to evaluate the opinions of graduates and students. The survey was sent to their email addresses and returned to the researcher after completion. Results: Kirkpatrick's evaluation model showed that the overall evaluation of the operating room program was 70.97 ± 9.32, which can be considered a moderate level. Students' satisfaction with the program was moderate (68.00 ± 14.97); their learning (84.54 ± 15.69) and performance (84.30 ± 9.28) were evaluated to be at a reasonable level. Conclusion: Considering the average effectiveness of the whole program, it is suggested that the educational managers of the operating room department plan and attempt to increase their indicators by considering the weaknesses and strengths of the program.